The Problem of Rational Political Decision-Making in Thucydides’ History (2.60-64) - Čekavičius, Laisvūnas (Literatūra, 2025)
The article analyses Pericles’ last speech in Thucydides’ History (2.60–64) as a case revealing the limits of rational political decision-making in a crisis situation. Although Pericles seeks to convince the Athenians to continue the war by using rational arguments, there is a fundamental contradiction in his rhetoric: his belief in the unlimited power of Athens at sea. This motif, which did not influence the mood of the citizens at the time, later became the ideological basis for an expansionist policy that led to the collapse of the polis. The article argues that Thucydides deliberately creates an ambiguous portrait of Pericles: his speech simultaneously expresses efforts to preserve the state and shapes the ideology that undermines it. The analysis is based on Thucydides’ decision-making scheme (1.75.3, 1.76.2), which reveals how Pericles’ rhetoric clashes with the emotional response of society. The speech takes on a tragic dimension, and the figure of Pericles highlights the limits of human and community political thinking.
Keywords: Thucydides; Pericles; Athenian Empire; decision-making